Modern research on the extraction of biologically active substances from plant raw materials using enzymes - A. A. Fabritskaya; S. O. Semenikhin; V. O. Gorodetsky; N. I. Kotlyarevskaya; E. P. Victorova (Новые технологии, 2021)
The article overviews modern studies of domestic and foreign scientists in the field of extraction of biologically active substances from plant materials using enzymes. Extraction of biologically active substances using enzymes allows for controlled biotransformation of plant materials due to the precise specificity and selectivity of enzymes, which creates mild conditions that ensure the preservation of biologically active substances. It has been noted that the quality of the extractant used has a significant effect on the efficiency of the extraction process. Thus, raw materials treated with a combination of an electrolyte and an enzyme are extracted more efficiently by reducing the mass transfer barrier. The main advantage of using supercritical fluids as an extractant is a decrease in temperature or pressure that leads to the precipitation of the extractable substance. One of the main disadvantages of the process of extracting biologically active substances from plant materials using enzymes is their high cost. To eliminate this disadvantage, the following intensification methods are used: ultrasonic treatment, high pressure treatment and microwave treat- ment. The most promising methods for intensifying the process of extracting biologically active substances from plant materials using enzymes are methods of ultrasonic and microwave treatment. Ultrasonic treatment under optimal conditions allows increasing the activity of enzymes, and microwave treatment provides more efficient penetration of the extractant into the tissues of plant material, due to the destruction of cell walls.